2011
DOI: 10.1007/s12011-011-8994-0
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and l-Carnitine Reduce Oxidative Stress in the Heart of Rat Induced by 2.45-GHz Radiation from Wireless Devices

Abstract: The aim of this study was to investigate the possible protective role of selenium and L-carnitine on oxidative stress induced by 2.45-GHz radiation in heart of rat. For this purpose, 30 male Wistar Albino rats were equally divided into five groups namely controls, sham controls, radiation-exposed rats, radiation-exposed rats treated with intraperitoneal injections of sodium selenite at a dose of 1.5 mg/kg/day, and radiation-exposed rats treated with intraperitoneal injections of L-carnitine at a dose of 1.5 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 31 publications
2
8
0
2
Order By: Relevance
“…Thus, the effectiveness of some antioxidants for mitigation of RFR exposure effects was demonstrated. Such protective effects have been reported for melatonin [21][22][23][24][25], vitamin E and C [26,27], selenium and L-carnitine [28].…”
Section: Introductionsupporting
confidence: 53%
“…Thus, the effectiveness of some antioxidants for mitigation of RFR exposure effects was demonstrated. Such protective effects have been reported for melatonin [21][22][23][24][25], vitamin E and C [26,27], selenium and L-carnitine [28].…”
Section: Introductionsupporting
confidence: 53%
“…Gumral et al, 2009; Türker et al, 2011. Nazıroğlu et al 2012 observed proliferative effects of 2.45 GHz EMR on human leukaemia cancer cells through the overproduction of reactive oxygen species (ROS) and Ca 2 + influx [9][10][11]. In addition, Aynali et al (2013) showed that WIFI (2.45 GHz) EMR (for 1 h/day for 30 days) increased lipid peroxidation levels in laryngotracheal mucosal tissues of rats [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the irradiated rats treated with LC 1.5 mg/kg b.w, i.p. concentrations of vitamins E were higher than in those rats that were only exposed to 2.45-GHz radiation [106]. Furthermore, metabolomics analysis shows that α-tocopherol deficiency in rats was associated with a compensatory increase in carnitine content in the liver [107].…”
Section: Sparing Effects Of Carnitine On Vitamin Ementioning
confidence: 89%